Cardiorenal Syndromes and Their Role in Water and Sodium Homeostasis - Burýšková Salajová, Kristína; Malík, Jan; Valeriánová, Anna (Physiological research, 2024)
Sodium is the main osmotically active ion in the extracellular fluid and its concentration goes hand in hand with fluid volume. Under physiological conditions, homeostasis of sodium and thus amount of fluid is regulated by neural and humoral interconnection of body tissues and organs. Both heart and kidneys are crucial in maintaining volume status. Proper kidney function is necessary to excrete regulated amount of water and solutes and adequate heart function is inevitable to sustain renal perfusion pressure, oxygen supply etc. As these organs are bidirectionally interconnected, injury of one leads to dysfunction of another. This condition is known as cardiorenal syndrome. It is divided into five subtypes regarding timeframe and pathophysiology of the onset. Hemodynamic effects include congestion, decreased cardiac output, but also production of natriuretic peptides. Renal congestion and hypoperfusion leads to kidney injury and maladaptive activation of renin-angiotensin-aldosterone system and sympathetic nervous system. In cardiorenal syndromes sodium and water excretion is impaired leading to volume overload and far-reaching negative consequences, including higher morbidity and mortality of these patients. Keywords: Cardiorenal syndrome, Renocardiac syndrome, Volume overload, Sodium retention.
Keywords: Animals; homeostáza; Kidney; voda; lidé; Cardio-Renal Syndrome; Sodium; zvířata; Water; vodní a elektrolytová rovnováha; Homeostasis; kardiorenální syndrom; sodík; ledviny; Water-Electrolyte Balance; Water-Electrolyte Imbalance; vodní a elektrolytová nerovnováha; Humans